PENGARUH DURASI SERANGAN GELOMBANG TERHADAP TINGKAT KERUSAKAN LAPIS LINDUNG PEMECAH GELOMBANG - Ida Bagus Agung (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2015)
this research tetrapod  have been utilized for breakwater  cover layer or armour layer. The effect of wave duration on the armor  layer tetrapod stability was  studied. The models were run  in the irregular wave flume, where Bretschneider spectrum may be generated attacking  the breakwater. The waves were set to break before reaching the breakwater. The test was conducted until the damage level of armour layer reached more than 5 %. The result of the research showed that waves duration and the high  of the wave attack affect the stability of armour layer, especially when the wave  was Rayleigh distributed. The effect of waves duration  reduced  as more and more waves broken before reaching the structure of the breakwater